Evidence of metal–organic coordination between Fe and flavonoid chrysin in a green anticorrosion film. Issue 1 (31st December 2022) - Díaz-Cárdenas, María Yesenia; Uruchurtu Chavarín, Jorge; Valladares Cisneros, María Guadalupe; Lagunas-Rivera, Selene; Menchaca Campos, Elsa Carmina
ABSTRACT: This work shows interesting results for a metal–organic complex as a green corrosion inhibitor. The study describes features of two passive films (PF) containing chrysin for mild steel in H2 SO4 by means of electrochemical noise under a potentiostaic regime as a function of time. The features showed a current reduction due to the formation of a passive film with better stability and homogeneity when chrysin is absorbed at the optimal experimental potential. PF formed at 50 ppm presented a very high corrosion protection over seven hours reducing the current density seven orders of magnitude, and PF formed at 300 ppm showed two orders of magnitude decrease over 23 h. PF analysis by FT-IR spectra showed important stretch band shift vibrations in the carbonyl and hydroxyl groups as evidence of the presence of metal–organic complex. Moreover, the information provided by adsorption isotherms and quantum chemical calculations confirmed the coordinated bonds established by chemisorption process which correlates with the experimental results. GRAPHICAL ABSTRACT: UF0001